Efficacy, Safety, and Economics of Innovative Medicines: The Role of Multi-Criteria Decision Analysis and Managed Entry Agreements in Practice and Policy - Fens, Tanja; van Puijenbroek, Eugène P.; Postma, Maarten J. (Frontiers in Medical Technology, 2021)
NA